Seeing the Invisible: The Value of Bone Scan to Distinguish Chondroblastic Osteosarcoma From Prosthesis Loosening. (13th August 2021) - Chuang, Tzyy-Ling; Chen, Yu-Ruei; Wang, Yuh-Feng
Abstract: A 76-year-old woman with uterine cervical cancer 20 years ago received right total hip replacement 3 months ago for right hip avascular necrosis without specific intraoperative finding. She reported persistent right hip pain after falling from bed. Pelvic x-ray showed right pubic ramus fracture. To evaluate prosthesis loosening, 99m Tc-MDP 3-phase bone scan was arranged, showing diffusely and heterogeneously increased vascularity and tracer perfusion over the right hip, with intensely and heterogeneously increased metabolism in the right iliac bone and hip. SPECT/CT showed nearby swelling of calcified muscles. After debridement and synovectomy, the pathologic report showed chondroblastic osteosarcoma.